PENGARUH PERSEPSI MASYARAKAT TERHADAP KECEMASAN KAUM HOMOSEKSUAL/LESBIAN - Siti Zahra Bulantika (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2017)
Indonesia is the country which does uphold norms and values of its people. Homosexual/Lesbian for most of eartern people is declared as not common sexual orientation. Negative stigma from people caused social anxious for homosexual community. For minority anxiouses show up all togather with attact or negative perpective from society, the strict eastern culture with binding social norms, will give social punishment to individual deviant behaviour such as homosexialbehaviour through humiliation to isolation. This condition become the main problem for homosexual community. They feel that they as minority. Though there is a proggres of confession over homosexual community rights, research on history, sosiology, and psycology show there is hobiophobia and sxual prejudice from all over the world. Utilization of sources, demograpics, and high ducation evidently efffect the perception over minority. For professional or institution that shade homsexual, it is expected to be able to give psychoeducation, training, or any other intervansion that are able to reeducate social anxious homosexual/lesbian community. We can prevent through rehabilitaion or briefing to to this community